Bone Response to High-Intensity Interval Training versus Moderate-Intensity Continuous Training in Adolescents with Obesity - Julian, Valérie (2022)
Introduction: Since adolescents with obesity are prone to bone fragility during weight loss, the aim was to compare the impact of high-intensity interval training (HIIT) versus moderate-intensity continuous training (MICT) on bone density, geometry, and strength. Methods: Sixty-one adolescents were randomly assigned to 2 cycling trainings (HIIT and MICT) and a control (CTR, without training) group. Anthropometry, dual-energy X-ray absorptiometry with hip structural analysis and the trabecular bone score (TBS) were assessed before and after the 16-week intervention. Results: Body mass index (BMI) and fat mass (FM) percentage decreased at T1 versus T0 in both training groups (p < 0.001 for HIIT, p = 0.01 for MICT), though to a larger extent in HIIT (p < 0.05). Total body bone mineral density (BMD) and bone mineral content (BMC) increased in both training groups (p < 0.001), but to a greater extent in HIIT for BMC (p < 0.05). Lumbar spine BMD and BMC increased in both training groups (p < 0.001 for HIIT, p < 0.01 for MICT), with a time × group interaction between HIIT and CTR (p < 0.05) only. TBS increased in both training groups (p < 0.01 for HIIT, p < 0.05 for MICT). Hip BMD and BMC increased in both HIIT (p < 0.001 and p < 0.01) and MICT (p < 0.01 and p < 0.05). At the narrow neck (NN), endocortical diameter, width (p < 0.01), cross-sectional moment of inertia, and section modulus (Z) (p < 0.05) increased only in the HIIT group, such as BMD and Z (p < 0.05) at the intertrochanteric region (IT) and average cortical thickness (p < 0.001) and width (p < 0.05) at the femoral shaft. At the NN and IT, the buckling ratio decreased only in the HIIT group (p < 0.05), predicting higher resistance to fracture. Conclusions: In addition to inducing greater BMI and FM percentage decreases in comparison to MICT, HIIT improves multisite bone density, geometry, and strength, which heighten the justification for HIIT as part of weight loss interventions in adolescents with obesity.